2021
DOI: 10.1002/ijgo.13992
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of same‐day discharge after minimally invasive hysterectomy for benign indications

Abstract: Objective: To identify predictors of same-day discharge after benign minimally invasive hysterectomy. Methods:In this retrospective cohort study, we identified women (n = 1084) undergoing benign minimally invasive hysterectomy from 2009 to 2016. Multivariate logistic regression was used to examine demographic, operative, and surgeon factors associated with discharge on postoperative day 0.Results: In our study population, 238 women (22%) were discharged on the same day.Robotic hysterectomy (risk ratio [RR] 2.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…The meta-analysis showed that radical hysterectomy (OR: 3.46; 95% CI: 1.90–6.29; I 2 = 0.0%; Figure 5A ) was disadvantageous for SDD, while lymphadenectomy (OR: 1.70; 95% CI: 0.39–7.45; I 2 = 90.9%; Figure 6A ) and adhesiolysis (OR: 1.48; 95% CI: 0.91–2.41; I 2 = 56.0%; Figure 6B ) did not affect SDD ( 21 , 22 , 25 , 27 , 29 , 30 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The meta-analysis showed that radical hysterectomy (OR: 3.46; 95% CI: 1.90–6.29; I 2 = 0.0%; Figure 5A ) was disadvantageous for SDD, while lymphadenectomy (OR: 1.70; 95% CI: 0.39–7.45; I 2 = 90.9%; Figure 6A ) and adhesiolysis (OR: 1.48; 95% CI: 0.91–2.41; I 2 = 56.0%; Figure 6B ) did not affect SDD ( 21 , 22 , 25 , 27 , 29 , 30 ).…”
Section: Resultsmentioning
confidence: 99%
“…There was no difference in rates of SDD between Black and White patients (OR: 1.11; 95% CI: 0.79–1.56; I 2 = 54.0%; Figure 4A ), between Hispanic and non-Hispanic people (OR: 0.66; 95% CI: 048–0.91; I 2 = 59.0%; Figure 4B ), and between smoking and non-smoking populations (OR: 1.02; 95% CI: 0.88–1.19; I 2 = 0.0%; Figure 4C ) ( 5 , 19 , 25 , 29 , 30 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 40 Some factors can be modified to increase the same day discharges which eliminate the cost of the hospital stay and decrease the overall hospital costs. 41 Looking specifically at robotic hysterectomy, Borahay et al found that outpatient hysterectomy can be significantly cost-effective for the institution investing in the robotic surgery platform. 40 On a larger scale, a systematic review and meta-analysis of eight studies found that outpatient hysterectomy had a low overall re-admission and complication rate.…”
Section: Proposed Cost Containment Strategiesmentioning
confidence: 99%